1999
DOI: 10.1007/s001130050395
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injuries complicating osteosynthesis in proximal femur fractures

Abstract: While there are quite a number of reports on vascular injuries complicating hip arthropasty by acetabular component screw fixation, retractor tip pressure or extruding bone cement, the incidence of deep femoral vessel injuries in operative fixation of proximal femoral fractures is comparatively seldom described. We report on two patients with per- and subtrochanteric femoral fractures who sustained injuries of deep femoral artery branches during the implantation of a dynamic hip screw (DHS) and a dynamic condy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…13,14 Manner et al emphasized that traction on a fracture table tightens the femoral muscles and additionally reduces the local mobility of the DFA. 15 Yang et al demonstrated the influence of the extremity’s position on the fracture table on the distances between femoral vessels and the medial femoral cortex. The mean distance between the SFA and the bone diminished significantly when the leg was brought into adduction of 20° on a traction table (reduction position) from 20.2 mm to 11.8 mm and even to 9.4 mm with an additional internal rotation of 20°, thus predisposing it to injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Manner et al emphasized that traction on a fracture table tightens the femoral muscles and additionally reduces the local mobility of the DFA. 15 Yang et al demonstrated the influence of the extremity’s position on the fracture table on the distances between femoral vessels and the medial femoral cortex. The mean distance between the SFA and the bone diminished significantly when the leg was brought into adduction of 20° on a traction table (reduction position) from 20.2 mm to 11.8 mm and even to 9.4 mm with an additional internal rotation of 20°, thus predisposing it to injury.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is imperative to stay in close contact with the bone surface while passing the instrument and also to maintain the position of the dorsal half of the cerclage passer (Synthes) against the bone while bringing and engaging the ventral half to it. 9 Other precautionary measures could include reducing the amount of traction 15 as well as the amount of adduction and internal rotation 16 and also restricting the number of passes 4 in order to safeguard the vasculature during this procedure. We recommend strict vigilance for any undue bleeding particularly when the two halves of the cerclage passer (Synthes) are clamped together or when the two halves are disengaged and being removed.…”
Section: Discussionmentioning
confidence: 99%
“…Contusions of the musculoskeletal system are among the commonest causes of emergency-room consultation. Vascular injury should be suspected in all patients with a history of trauma, including non-high-energy trauma, when haemodynamic instability appears [ 1 4 ]. At this point, additional studies need to focus on locating the affected area, and the patient should be admitted to intensive care to ensure that there is no deterioration of vital signs.…”
Section: Discussionmentioning
confidence: 99%
“…Acute vascular injuries have been described in relation to high-energy accidents in patients who are polytraumatised or undergoing surgery in the femoral area [ 1 4 ], but this diagnosis is very rare in young patients with no relevant medical history. In such cases, clinicians should be alert to the possibility of structural alterations in the vessels that predispose them to injury or impaired blood clotting [ 5 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 Drill bit overpenetration can result in clinically relevant damage to nerves, tendons, and vessels, which negatively impact and complicate surgical outcomes. 8 9 10 , 11 , 12 13 …”
mentioning
confidence: 99%